2018
DOI: 10.1007/s00276-018-2124-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-anatomic mapping of the tarsal tunnel with regard to Baxter’s neuropathy in recalcitrant heel pain syndrome: part I

Abstract: Purpose Neuropathy of the Baxter nerve (BN) seems to be the first cause of the heel pain syndrome (HPS) of neurological origin. Methods 41 alcohol–glycerol embalmed feet were dissected. We documented the pattern of the branches of the tibial nerve (TN) and describe all relevant osteofibrous structures. Measurements for the TN branches were related to the Dellon–McKinnon malleolar-calcaneal line also called DM line (DML) for the proximal TT and the Heimkes Triangle for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 33 publications
6
70
0
3
Order By: Relevance
“…The inferior calcaneal nerve is also known as the rst lateral plantar nerve, the little toe abductor nerve or the Baxter nerve [32][33][34]. Moroni [13], Oliva [35] and Govsa [11] all found that the occurrence rate of this nerve was 100%. In our reconstructed image, the display rate was 95%, and the anatomical data showed that the cross-sectional diameter at the beginning of the subcalcaneal nerve was (1.4 ± 0.5) mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferior calcaneal nerve is also known as the rst lateral plantar nerve, the little toe abductor nerve or the Baxter nerve [32][33][34]. Moroni [13], Oliva [35] and Govsa [11] all found that the occurrence rate of this nerve was 100%. In our reconstructed image, the display rate was 95%, and the anatomical data showed that the cross-sectional diameter at the beginning of the subcalcaneal nerve was (1.4 ± 0.5) mm.…”
Section: Discussionmentioning
confidence: 99%
“…At present, through the anatomic study of the tibial nerve and its branches at the ankle canal, the location and course of the nerve are determined, and the origin and quantity of the medial calcaneus nerve and the inferior calcaneus nerve at the ankle canal are classi ed [9][10][11], which provides a great help for the understanding of the nerve in the ankle canal. Using ultrasound to display the nerves in this area, and the injection of infracalcaneus nerve under the guidance of ultrasound can improve the injection accuracy [12,13], but ultrasound can not display the whole shape of the nerves in a stereoscopic and intuitive way, and largely depends on the technology and experience of the operator. Some studies to initially discuss the display and diagnostic value of the ankle canal tibial nerve and branch thtough MR [14,15].Because of the 2D sequence and routine transverse, coronal and sagittal scanning, it is di cult to show and trace the tibial nerve and its branches in a large range on the same plane, and it is di cult to show the small branches clearly, and no more comprehensive study on the morphological types of medial calcaneus nerve and inferior calcaneus nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Translational peripheral nerve anatomy is studied through different methods such as macroscopic cadaveric dissections, surgical interventions, electrodiagnostic studies, and laboratory research (Mazurek and Shin, ; Konschake et al, ; Schulz et al, ; Bendella et al, ; Hausott and Klimaschewski, ; Moroni et al, ). Macroscopic anatomic research itself is often criticized for not providing novel scientific results (Mazurek and Shin, ; Lippert, ).…”
Section: Application Of Ionm and Ultrasonography In Thyroid Surgerymentioning
confidence: 99%
“…Macroscopic anatomic research itself is often criticized for not providing novel scientific results (Mazurek and Shin, ; Lippert, ). In contrast, over the years, a number of scientific questions concerning clinical and applied peripheral nerve anatomy have been raised and addressed with direct benefit for the patient (Eichenberger et al, ; Dralle et al, ; Konschake and Fritsch, ; Konschake et al, ; Konschake et al, ; Fernández‐Gibello et al, ; Konschake, ; Moroni et al, ). For example, the inferior laryngeal nerve (ILN) in endocrine surgery (Chiang et al, ; Konschake et al, ; Randolph and Kamani, ) and peripheral nerves of the head and neck in migraine surgery (supraorbital, supratrochlear, auriculotemporal, zygomaticotemporal, and occipital) have been in the focus of several studies (Mosser et al, ; Guyuron et al, ; Totonchi et al, ; Janis et al, , et al; Caruana et al, ; Berchtold et al, ; Gfrerer and Guyuron, ).…”
Section: Application Of Ionm and Ultrasonography In Thyroid Surgerymentioning
confidence: 99%
“…At present, through the anatomic study of the tibial nerve and its branches at the ankle canal, the location and course of the nerve are determined, and the origin and quantity of the medial calcaneus nerve and the inferior calcaneus nerve at the ankle canal are classified [9][10][11], which provides a great help for the understanding of the nerve in the ankle canal. Using ultrasound to display the nerves in this area, and the injection of infracalcaneus nerve under the guidance of ultrasound can improve the injection accuracy [12,13], but ultrasound can not display the whole shape of the nerves in a stereoscopic and intuitive way, and largely depends on the technology and experience of the operator. Some studies to initially discuss the display and diagnostic value of the ankle canal tibial nerve and branch thtough MR [14,15].Because of the 2D sequence and routine transverse, coronal and sagittal scanning, it is difficult to show and trace the tibial nerve and its branches in a large range on the same plane, and it is difficult to show the small branches clearly, and no more comprehensive study on the morphological types of medial calcaneus nerve and inferior calcaneus nerve.…”
Section: Introductionmentioning
confidence: 99%